(untitled) (Archives of Criminology, 1984)
The results of empirical studies on general deterrence carried out so far are far from being unequivocal. Taking general deterrence research as a whole, it can be concluded only that in some situationa some individuals are deterred from some crimes by some punishments. Moreover, it is now obvious to most researchers that the problem is not whether punishment has deterrent effects but rather under what conditions and to what extent they occur. Thus, as the deterrent effects of the punishment threats are tentatively confirmed, further studies in this direction seem to be called for. So far the main achievement of the general deterrence studies has been overcoming some simplified approach to formulating problems (in research) and improvement in research methods rather than verification of hypotheses. Therefore, instead of describing the results of these studies, this paper has been limited to methodological problems. It seems to the author that with the present-day knowledge on the deterrent effeets of punishment threats, the above approach will help to ensure continuation of empirical studies and will contribute to the gradual and cumulative enrichment of theoretical interpretations of the abovementioned problem. Owing to the limited scope of this presentation only some selected problems have been dealt with. While carrying out this selection the author had to bear in mind that no such empirical studies had been carried out this selection the author had to bear in mind that no such empirical studies had been carried out in poland so far and the results of studies made elsewhere had not become popular among Polish readers. This article has been confined to the penal law and the deterrent effects of criminal punishment threats rather than the punishment in general and it was mostly based on works published in the English language. Apart from the Introduction, the article consists of the following parts: I. Notion of general deterrence, II. Deterrence vs. other general preventive effects of punishment, III. Types of general deterrence, IV. Theoretical foundations of general deterrence research, V. Conditions for effective general deterrence, and Summary. I. Notion of general deterrence The author points to the differences in the definition of general deterrence, to the ambiguity and vagueness in the formulations found in the literature on this subject. She stresses the importance of a clear definition of the above notion for the purposes of empirical studies, which will, as a result, help to avoid misunderstanding in interpreting the research evidence. Since punishment, or strictly speaking, the threat of punishment, prevents people from committing an offence in a variety of ways, the deterrent being only one of them, the researcher should clearly define what mechanisms he is going to study. For empirical studies a narrow definition of general deterrence, i.e., restriction to one mechanism only, seems to be more appropriate. So far, most studies have been devoted to the mechanism of deterrence. II. Deterrence vs. other general preventive effects of punishment At this point the author discusses also other mechanisms of the preventive effect of punishment threats, especially its moral and educational influence as well as its role in habit formation. Many mechanisms of general preventive effect of punishment have not yet even been identified. In spite of the fact that it is advisable to restrict the subject of investigation to but one mechanism, it is difficult in practice to differentiate between the various mechanisms of general prevention. When interpreting the data it will probably be necessary to determine the impact of these other processes on the results of investigations. The study of the other general preventive effects of criminal sanctions brings about some specific problems such as those of a diffcrent time perspective, as they are of no direct character and require some longer period of time to bring down the crime rate. Although the present paper is confined to the effects of criminal sanctions, the author emphasizes the need for considering a wider perspective of reasons for compliance with the law. III. Types of general deterrence. When considering general deterrence from the terminological point of view one has to include its various types. The author discusses the following types of general deterrence encountered in literature: quantitative vs. qualitative; absolute vs. marginal; particularized vs. generalized or selective; total or complete vs. restrictive; replacing vs. non-replacing partial vs. Modifying or substituting or displacing. The distinctions suggested are often neither exhaustive nor exclusive. Still the general deterrence typology even in this form is of considerable methodological importance. Different types of evidence are relevant when an attempt is made to determine the different types of general deterrence. If the distinctions are not made then it may be concluded that a sanction had no deterrent effect at all simply because no evidence was collected for what is only one type of general deterrence. IV. Theoretical foundations of general deterrencę research. First the author presents the deterrence doctrine. It is because what lies at the foundation of general deterrence research, i.e., a set of loosely connected and vague statements and assumptions, can at most be called a doctrine. Besides, the present shape of this doctrine does not differ much from that of the classical model of general deterrence formulated by C. Beccaria and J. Bentham. The drawbacks and ambiguities of the deterrence doctrine, as pointed out by the author, have come to bear on the results of studies aimed at the verification of the doctrine’s propositions. What is necessary is to reformulate the deterrence doctrine into an empirical theory. Then, directions are discussed in which the deterrence doctrine has been and still is developing. First of all, the deterrence doctrine is being developed through a different conceptualization of the relationship between legal sanction and behaviour. It is now generally agreed that general deterrence cannot be conceptualized as a unitry bivariate relationship between punishment threats and crime. Instead, it is maintained that the relationship is moderated by a number of conditions yet to be identified empirically. The number of variables to be considered have also become larger. What is specially worth noting is the fact that other, extralegal factors have been included in deterrence models. Another important trend in the development of the deterrence doctrine is that of emphasizing its psychological character and including the so-called perceptual variables characterizing the way how sanction characteristics are perceived by potential offenders. The emphasis on perceptions of punishment developed from an awareness that deterrence is a communicative proces. In order to deter, actual threats of legal punishment must be communicated to individuals. It will be most essential for the formulation of the general deterrence theory to determine the relationship between objective properties of legal sanctions. V. Conditions for effective general deterrence. The basic research problem consist in identifying the conditions for effective general deterrence. As for determining these conditions, there are so far only few empirical data available. Besides, one can hardly see what the consistent theoretical assumptions could be which will help to have some relevant factors included in the study, especially in the case of extralegal conditions. One should also be aware of the fact that the numer of possibly relevant factors is, practically speaking, unlimited and that many of these factors will influence behavior only when particural values of a large number of the others are present. But, characteristic of most „theoretical” writings is that the authors usually confine themselves to summing up a list of possible relevant factors, not dealing with possible interaction. The author discusses the concept of a „marginal group”. Summary The article ends with a short description of the methods used in the study on general deterrence. The author points out to limitations of the methods and data that have most frequently been used in addressing the deterrence question. It is necessary to collect better data about perceptual processes.